The Design and Implementation of 60 GHz Millimeter Wave Communication System for FWA - Kan, Lichen (My University, 2023)
With the high-speed development of the Internet, people's demand for data transmission speed is getting higher and higher. At present, China has basically completed the construction of the core network of optical fiber as the main communication network. The transmission speed of fiber optic communication is extremely fast and can meet the current user demand for high-speed Internet services. However, due to the limitation of access technology, the communication performance from the optical node to the user terminal is greatly restricted, and the communication services that users can enjoy are far from the expected. Based on the millimeter wave communication technology in 60 GHz band, this thesis aims to provide a fixed wireless access solution with low-cost, simple deployment and high transmission performance to solve the last-mile problem in the scenario described above. The thesis focuses on the following work： Complete the hardware platform design of the millimeter wave communication system. Complete the design of the software system of the communication network. The main work is divided into the construction of the wireless network framework and the millimeter wave communication link. In the first part, the focused tasks were to build the software base environment and complete the driver development, porting and initialization. After that, the point-to-point communication link was successfully established and the configuration of communication nodes was completed, and the relevant network parameters were set. Optimize the performance of the communication system. After completing the design of the hardware and software, several performance optimization schemes are proposed mainly for communication rate and link immunity with the aim of achieving a trade-off between transmission rate and link quality. After optimization, the results of the point-to-point communication tests meet the study objectives. From the perspective of engineering applications, this thesis designs the basic functions of the millimeter wave communication system for the fixed wireless access field in order to solve the last mile problem. Meanwhile, it systematically describes the process of its hardware and software implementation, and gives the testing and optimization scheme.